Endowments and Their Cultural and Educational Role in Egypt During the Reign of Muhammad Ali (1805-1848) (مجلة وقف في دراسات الاوقاف, 2026)
In this chapter, the researcher presents the proposed frameworkfor the current study, focusing on the general goal of establishingpractical mechanisms to achieve financial sustainability for theendowments of Saudi universities. Additionally, the chapter providesa summary of the study’s results, key related recommendations, andsome suggestions for future research.